1999
DOI: 10.1007/s002619900567
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution magnetic resonance imaging of the anorectal region without an endocoil

Abstract: High-resolution MRI of the anorectal region without an endoluminal coil is feasible. The MR technique with an external phased array coil allows detailed imaging of the anal sphincter at rest, the rectum, and the surrounding pelvic structures with one single investigation. The results are promising and suggest useful applications in the management of anorectal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 24 publications
0
30
1
3
Order By: Relevance
“…Recent research has evaluated the role of high-resolution MRI of the anal sphincter using phased-array coils [27]. This study has demonstrated the potential value of this technique, but its role in anal incontinence has yet to be determined.…”
Section: Techniquementioning
confidence: 97%
“…Recent research has evaluated the role of high-resolution MRI of the anal sphincter using phased-array coils [27]. This study has demonstrated the potential value of this technique, but its role in anal incontinence has yet to be determined.…”
Section: Techniquementioning
confidence: 97%
“…L'endo-IRM [24,39,56,57] ou I'IRM externe en r6seau phas6 [58] semblent 6galement capables d'6valuer l'appareil sphinct6rien. Un d6fect apparalt comme une interruption de la continuit6 de l'anneau musculaire et une cicatrice fibreuse comme une zone en hyposignal [59][60][61].…”
Section: Evaluation De L'appareil Sphinct~rienunclassified
“…Further, MR imaging was recently found to have added value as compared with the clinical assessment of patients with perianal fistulas [20]. The results of these studies [2,3,5,19] in addition to the preliminary findings by Beets-Tan et al [1] suggest that MRI could serve as part of the preoperative assessment of anorectal diseases. The diagnostic information provided by MRI prior to any surgical procedure or during the postoperative follow-up may improve the clinical and surgical management in patients with anorectal diseases S. M. Hussain and E. K. Outwater: MRI of the anorectal region 583 and may help to reduce the occurrence of complications.…”
mentioning
confidence: 91%
“…In this respect, the report by Beets-Tan et al in this issue of Abdominal Imaging is interesting [1]. Beets-Tan et al performed a feasibility study to assess the ability of the spine phased array coil in depicting the normal anatomy and abnormalities of the anorectal region.…”
mentioning
confidence: 95%
See 1 more Smart Citation